Separating arsenic oxyanions from natural waters for oxygen isotope analysis - Tang, Xiaohui (Karlsruher mineralogische und geochemische Hefte : Schriftenreihe des Instituts für Mineralogie und Geochemie, 2013)
This study has developed a complete procedure for the measurement of oxygen isotopes in arsenic oxyanions in natural waters by using different adsorbents. The experimental results of kinetic exchange of oxygen between AsO43- and water show that the entire exchange procedure happens in a very short time at different pH conditions and temperatures.